Web-based Learning Media “ESL Games” to enhance Students’ English Learning Vocabulary - Rezza Chaidir (Publikasi Indonesia, 2021)
This study aims to improve eighth-grade students' mastery of English vocabulary by students in junior high school in the 2021 academic year through web-based English learning. This study also aims to determine the effectiveness, efficiency, and attractiveness of Web-based English Learning in the learning of English. This was carried out at State Junior High School (SMPN) 4 of Mandau from August to October 2021 using a proactive action research method based on the John Elliot model. This study was carried out in three classes that served as representatives for the other six classes, namely class 8.4, 8.6, and class 8.8, with around 30 students in each class as a randomly selected sample. A mixed technique approach was used to collect and analyze data. In this study, questionnaires, documents, observations, interviews, and tests were used to collect the data. The results revealed that web-based English Learning could improve students' English vocabulary. Furthermore, it is effective, efficient, and entertaining to use in English learning for eighth graders.